DAMPAK DIMENSI EKUITAS MEREK DALAM MEMBENTUK MINAT BELI ULANG - Vera Verdilla; Albari Albari (Jurnal Manajemen Maranatha, 2018)
Along with the times, the economy grew by leaps and bounds. Many brands are popping up in the market. Brands competing to attract the attention of consumers. To cope with competition management must first understand the importance of the power contained within the dimensions of their brand equity. For that empirical research is intended to explain the relationship between the dimensions of brand equity, especially the positive influence of consumer repurchase intention. The population in this study are those who have never made a purchase in the clothing brand "G" in Yogyakarta. The sample involved is as much as 166 respondents with a sampling technique in the form of convenience sampling. Variable data used for the analysis is brand awareness, brand image, perceived quality, brand loyalty, and purchase intention. Data were analyzed using multiple linear regression, which is equipped with six types of test data analysis. The results of data analysis showed that brand awareness and brand image positive and significant impact on the perceived quality of the brand. Furthermore, brand awareness, brand image and perceived quality and significant positive effect on brand loyalty. The study also found brand awareness, brand image, perceived quality, brand loyalty and a positive and significant impact on the repurchase intention. In other words, awareness and a positive brand image can affect directly or indirectly (through the perceived quality and brand loyalty) to the repurchase intention.Â Keywords: Brand Awareness, Brand Â Image, Perceived Quality, Brand Loyalty, and Purchase Intention